(untitled) (Annals of Medical Research, 2021)
Aim: Depression is a multi-factorial disease characterized by a variety of symptoms. Individuals with psychiatric disorders are seem to be more prone to periodontitis. However, depression and periodontal disease can be considered bidirectional risk factors. Periodontal diseases can also be an effect on depression. The aim of this study is to determine the effect of non-surgical mechanical periodontal treatment on psychological state. Materials and Methods: Two randomized groups were established from depressed patients with non-treated periodontal diseases. Test (n = 92) and control group (n = 92). Clinical periodontal and psychological measures were administered at baseline and at 6 weeks in the control and test group. Periodontal treatment was applied to the test group. Results: After 6 weeks (the end of the periodontal therapy) there was a significant decrement in the results of Beck Depression Inventory (p a = 0.038) and a significant increment in Body Cathexis Scale (p a < 0.001) results in the test group. However, the results of Rosenberg Self-Esteem Scale (p a = 0.820) and Beck Anxiety Inventory (p a = 0.071) is similar between test and control groups. Conclusion: Within the limits of present study, the results suggest that periodontal treatment might be useful to improve depressive patients’ psychological conditions.